Green biosynthesis and physicochemical characterization of Fe3O4 nanoparticles using Punica granatum L. fruit peel extract for optoelectronic applications - Bouafia, Abderrhmane; Laouini, Salah Eddine; Tedjani, Mohammed Laid; Ali, Gomaa AM; Barhoum, Ahmed (Textile research journal, 2022)
Green biosynthesis of Fe3O4 nanoparticles (NPs) using plant extract is desired, as the plant extract is safe for humans and the environment. In this study, magnetite Fe3O4 NPs were greenly prepared using Punica granatum L. fruit peel extract as a reducing and capping agent. The effect of iron precursor contraction (0.01–0.1 M, FeCl3) was studied. The Fe3O4 crystalline with an average crystallite size range from 21 to 23 nm was proven by X-ray powder diffraction. Scanning electron microscopy images showed that the synthesized Fe3O4 NPs were mostly cubical. Ultraviolet-visible spectra showed that the prepared Fe3O4 NPs exhibit absorption at 270 nm related to the Fe3O4 NPs with a direct bandgap ranging from 1.87 to 2.26 eV and indirect bandgap of 2.16–2.48 eV. Fourier transform infrared spectroscopy analysis showed two characteristic absorption bands at 515 and 567 cm−1, which proved the successful formation of Fe3O4. The proposed method using Punica granatum L. fruit peel extract offers an economical and environmentally friendly route for synthesizing many other types of metal oxides.